MANAJEMEN MUTU TERPADU BERBASIS MAQASHID SYARIAH DI LEMBAGA PENDIDIKAN ISLAM - Feri Herdiana; M. Amrullah Azis; Annisa Fitri (Eduvis : Jurnal Manajemen Pendidikan Islam, 2024)
Islamic educational institutions are currently facing increasingly complex challenges in terms of quality improvement, particularly in integrating universal quality management values with Islamic educational principles. This study aims to construct a conceptual model of Total Quality Management (TQM) grounded in Maqashid Sharia as a comprehensive framework for quality improvement at Islamic educational institutions. Employing a qualitative library research methodology, this study systematically examines primary and secondary sources consisting of books, reputable scientific journals, and relevant policy documents. Data were gathered through systematic documentation techniques, followed by a content analysis approach to identify patterns, relationships, and constructs relevant to TQM and Maqashid Sharia. The findings demonstrate that the five principal elements of Maqashid Sharia—encompassing the preservation of religion (hifzh al-din), intellect (hifzh al-aql), lineage (hifzh al-nasl), life (hifzh al-nafs), and property (hifzh al-mal)—can be organically integrated into TQM dimensions covering curriculum, human resources, institutional culture, service quality, and financial management. This integration offers a more holistic, values-driven, and contextually relevant quality management model for Islamic education in Indonesia.